Największy pisarz argentyński - Kobyłecka-Piwońska, Ewa (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2014)
The paper presents Ricardo Piglia (b. 1940), one of the greatest writers of Latin America, and discusses his interest in Witold Gombrowicz.